2016
DOI: 10.1071/sr15085
|View full text |Cite
|
Sign up to set email alerts
|

Organic phosphorus speciation in Australian Red Chromosols: stoichiometric control

Abstract: Organic phosphorus (P) plays an important role in the soil P cycle. It is present in various chemical forms, the relative amounts of which vary among soils, due to factors including climate, land use, and soil type. Few studies have investigated co-variation between P types or stoichiometric correlation with the key elemental components of organic matter– carbon (C) and nitrogen (N), both of which may influence P pool structure and dynamics in agricultural soils. In this study we determined the organic P speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 55 publications
1
8
2
Order By: Relevance
“…1 contains prominent IP 6 peaks, especially for the two soils collected from above 1800 m above sea level (A1053 and A1054). This is in contrast to our previous studies on Australian soils where we noted the absence of, or relatively low intensity of, IP 6 peaks, which account for a relatively minor component (typically <12%) of the organic P in most Australian soils (Doolette et al 2011;McLaren et al 2014;Moata et al 2016). In previous studies, we reported that peaks due to a-and b-glycerophosphate have usually been larger than those of the IP 6 ; this is especially evident in the 31 P NMR spectra of Vertosols, for which IP 6 peaks were barely discernible (McLaren et al 2014).…”
Section: Discussioncontrasting
confidence: 55%
See 4 more Smart Citations
“…1 contains prominent IP 6 peaks, especially for the two soils collected from above 1800 m above sea level (A1053 and A1054). This is in contrast to our previous studies on Australian soils where we noted the absence of, or relatively low intensity of, IP 6 peaks, which account for a relatively minor component (typically <12%) of the organic P in most Australian soils (Doolette et al 2011;McLaren et al 2014;Moata et al 2016). In previous studies, we reported that peaks due to a-and b-glycerophosphate have usually been larger than those of the IP 6 ; this is especially evident in the 31 P NMR spectra of Vertosols, for which IP 6 peaks were barely discernible (McLaren et al 2014).…”
Section: Discussioncontrasting
confidence: 55%
“…By targeting soils from within the Australia-wide ASRIS database, samples from the highest altitudes of Australia were chosen to represent a series of typical alpine soils, which we hypothesised would exhibit spectral features in their 31 P NMR spectra more akin to those of soils from other relatively cold and wet locations. The composition of organic P in these alpine soils appears to differ to those previously reported for Australian soils (Doolette et al 2011;McLaren et al 2014;Moata et al 2016). In particular, the presence of phosphonates, which we identified in two of the soils at the coldest and wettest locations, have not been reported before in Australian soils but have been identified in cold, wet and acidic soils elsewhere where microbial activity is limited (Tate and Newman 1982;Zech et al 1987;Gil-Sotres et al 1990).…”
Section: Discussioncontrasting
confidence: 52%
See 3 more Smart Citations